Single staged treatment of a complex full thickness debridement for hidradenitis suppurativa using NovoSorb Biodegradable Temporizing Matrix™. Issue 3 (July 2022) - Malkoc, Aldin; Wong, David T.; Woodward, Brandon
Highlights: Treatment of full skin thickness debridement in high-risk patients using NovoSorb BTM can have satisfactory outcomes. NovoSorb BTM in large wounds with non-compliant patients has the potential to fully epithelize with only local wound care. Debridement of hidradenitis suppurativa and coverage using NovoSorb BTM for soft tissue coverage can yield great results. Abstract: Treatment of full skin thickness loss due to surgical debridement for difficult wound beds like necrotizing fasciitis and hidradenitis suppurativa (HS) is commonly treated using wide local excision and split-thickness-skin grafting or muscle flaps. Unfortunately, this strategy often leaves large soft tissue defects and can be complicated by infection and poor graft take, resulting in additional surgeries. Novel approaches using acellular dermal substitutes along with skin grafting are treatment options with favorable cosmetic outcomes and improve functionality by reducing contractures. However, patient non-compliance and various complications such as complex wound care, infection, product fragility and financial implications have contributed to a lack of widespread adaptation. NovoSorb Biodegradable Temporizing Matrix (BTM™) has been demonstrated to function as a dermal scaffold that has robust handling characteristics and requires minimal wound care. This case report describes the treatment course of a high-risk patient with poor nutrition and a history of a 20 pack-year tobacco smoking, methamphetamine use, phencyclidine use, and marijuana use with recurrent and widespread axillary, inguinal, and gluteal HS. This patient was treated using NovoSorb BTM™ as the primary dermal substitute without subsequent grafting to cover a 400 cm 2 left gluteal excision due to patient non-compliance. The covered area subsequently spontaneously epithelized after six months of local home health care during the COVID-19 pandemic. Our results show promise for future use of NovoSorb BTM™ to serve as a single stage surgery option to complete wound healing in high-risk patients.